Towards a Walkable City: Principal Component Analysis for Defining Sub-Centralities in the Santiago Metropolitan Area - Correa Parra, Juan Pablo.; Vergara Perucich, José Francisco.; Aguirre Núñez, Carlos. (MDPI, 2020)
This article presents a methodology for evaluating the potential for an urban area to become a 15-min city based on its existing essential urban functions. To elaborate this methodology, the research focused on the Metropolitan Area of Santiago de Chile, by identifying 28 urban functions and applying principal component analysis to review how these georeferenced variables are grouped into synthetic components that illustrate the walkability of each block concerning access to these functions. Variables are mapped by GIS software to review where concentrations of essential urban functions occur and where there is a need to increase availability of these missing uses. One of the findings of this study in the Metropolitan Area of Santiago is that essential urban functions provided by the state present a relatively equitable distribution in the metropolis. In contrast, essential urban functions provided by the market are highly concentrated in specific clusters, segregating walkability areas in the metropolitan space. The methodology presented here is replicable for other cities, and the findings offer a critical perspective on land management and urban planning for this case study, where normative frameworks must change to implement the 15-min city.
Keywords: 15-min city; Santiago; Chile; Urban governance; Amenities; Principal component analysis; Land use